Insight into healthcare design: lessons learned in two university hospitals. Issue 3 (4th July 2016) - Reijula, Jori; Reijula, Emmi; Reijula, Kari
Abstract : Purpose: Hospitals in the developed countries have been subjected to increasing economic pressure. Thus, several hospitals have been forced to improve their production efficiency while coping with limited resources. This paper aims to illustrate challenges and insight associated with health care (HC) facility design (FD) in two publicly funded hospitals. Design/methodology/approach: In this study, 14 interviewees from two Finnish university hospitals were interviewed. Both hospitals had implemented Lean methods and recently undergone rigorous renovation projects and were seen as ideal study targets. Findings: Both hospitals had managed to carry out successful indoor environment design. However, logistics, navigation, health information technology, scheduling, budgeting and outsourcing challenges had arisen. An outpatient care approach and customer-driven operational needs are beneficial and guide FD in the target hospitals. Lean thinking offers the necessary fundamental framework for integrating operational design as a part of FD. Research limitations/implications: Due to the relatively small sample size of the interviewees in this study, post occupancy evaluations in a larger target group should be conducted in the present hospitals. Furthermore, the communication with the interviewees may be considered qualitative due to the research approach based on interviews and content analysis. Practical implications: Hospital design should focus on developing aesthetic, durable and adaptable facilities that support work processes. The hospital management needs to ensure that architects and designers possess enough HC expertize and are able to interact with clinicians. FD projects should be led and organized more systematically, while project communication between all stakeholders should be more transparent and facilitated by – preferably – a hospital staff member. Furthermore, an organized forum for HC FD should be used for sharing knowledge. The clinicians must be thoroughly oriented to the new work environment and processes. Originality/value: This paper brings forth numerous crucial challenges and insight related to management of FD in two university hospitals.